Is service innovation different? - Aija Leiponen (The Research Institute of the Finnish Economy (ETLA), 2008)
This exploratory empirical study compares the determinants of innovation in manufacturing and services through descriptive and regression analyses of sales from innovative products and services. The results suggest that, contrary to earlier research, R&D investments play a positive and significant role in both services and manufacturing. Service firms also benefit from broad strategies of sourcing external information. In contrast, strategic breadth in terms of pursuing multiple different innovation objectives or cooperating with different types of partners appears to have detrimental effects on service innovation. We interpret the latter results through reference to service firms' R&D and alliance management capabilities: Managing multiple innovation projects or multiple cooperative arrangements is challenging, and some service firms may not have accumulated the requisite managerial capabilities to benefit from these strategies. The available data provide partial support for this conjecture.
Keywords: O31; O32; L8; 330; Dienstleistungssektor; Innovation; Innovationsmanagement; Regression; Finnland